Slides to Philosophy 167: Class 9 -- Descartes' Principia: The Vortex Theory of the Heavens -- Part 2. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 9, Part 2.